Peculiarities of relationships between the characteristics of psychophysiological adaptation of organism and criterion indicators of motor activity of modern students - Koval, Nataliia; Drezhenkova, Inna; Ocheredko, Oleksandr; Serheta, Ihor; Belov, Oleksandr; Redchits, Mykola (The Ukrainian Scientific Medical Youth Journal, 2023)
one of the priority components of the implementation of modern physiological and hygienic research is a prognostic assessment of the features of the leading characteristics formation of the adaptive resources state of the student’ organism based on the use of modern methods of statistical analysis in accordance with the conditions of stay, which differ in the features of the influence of health- creating factors, among which it is necessary to include level of motor activity. The purpose of the study was to determine the peculiarities of the relationships between the characteristics of psychophysiologi- cal adaptation and criterion indicators of motor activity of modern students based on the application ofcluster and factor analysis procedures. In the course of the scientific work 285 students (150 young wom- en and 135 young men) were supervised, who were divided into 3 comparison groups according to the level of motor activity. Individuals with high motor activity (group 1 of motor activity: 50 young women and 45 young men), medium motor activity (group 2 of motor activity: 50 young women and 45 young men) and low motor activity (group 3 of motor activity: 50 young women and 45 young men) levels were involved in their composition. As criterion indicators of motor activity, it was necessary to note the indicators of daily energy expenditure, which were estimated according to the timing-table method - up to 9000 kJ (low level of motor activity), 9000-11000 kJ (medium level of motor activity), more than 11000 kJ (high level of motor activity) among girls , and indicators of motor activity – up to 11,000 kJ (low motor activity level), 11,000-13,500 kJ (medium motor activity level), over 13,500 kJ (high motor activity level) among young men. Medical-sociological, epidemiological, psychophysiological, psycho- logical-pedagogical and statistical methods were used in the scientific work. In the course of the con- ducted research, based on the application of cluster and factor analysis procedures, the features of the relationships between the characteristics of the functional state and the level of development of psycho- physiological functions and, therefore, the leading characteristics of psychophysiological adaptation and criterion indicators of motor activity of modern students were determined. Data of cluster analysis procedures usage determined that the leading characteristics of the state of health and academic success were most significantly influenced by 3 leading clusters of characteristics of the psychophysiological adaptation of the students’ organism, namely: visual-motor speed, visual-sensory and integrative-coor- dination clusters. At the same time, based on the results of the application of factor analysis procedures, it was established that the most positive effect on the functional state of the organism of young women and young men was exerted by the movement regime characteristic of students, the values of daily energy expenditure of which vary between 9000-11000 kJ and between 11000-13500 kJ.